Edge Computing and Robotic Applications in Modern Agriculture - AYRANCI, AHMET AYTUĞ; Erkmen, Burcu (IEEE-Inst Electrical Electronics Engineers Inc., 2024)
The modernization of agricultural practices prominently features robotics as a key technology. Efforts are concentrated on achieving automation and enhancing efficiency in agriculture through advancements in robotic applications. The widespread integration of remote sensing systems into agricultural areas facilitates real-time information acquisition, enabling drones and robots to operate with enhanced efficiency and effectiveness. Robotics plays a crucial role in the evolution of agriculture 4.0 and agriculture 5.0 strategies, marking significant strides in agricultural technology. Specifically designed robots for agricultural use are currently employed in tasks like planting, fertilizing, irrigating, pest controlling, and harvesting, proving a certain level of effectiveness. Edge computing is crucial in enhancing efficiency and sustainability within modern agricultural practices. Edge computing can instantly process data from numerous devices, mitigating network congestion effectively. In modern agricultural applications, it is possible to perform multiple tasks in a coordinated and effective manner by using Unmanned Aerial Vehicle (UAV) and Unmanned Ground Vehicle (UGV) together. These devices can serve as both data collection and edge devices in the network. Multiple agricultural robot applications and benefits of these applications are explained in the study. © 2024 IEEE.
6th International Congress on Human-Computer Interaction, Optimization and Robotic Applications, HORA 2024
Keywords: Agricultural Robots; Agriculture 4.0/5.0; Autonomous Farming; Cooperative Robotics; Edge Computing